The Stone Master by Lesya Ukrainka: The Imagology of Don Juan’s Image in the Context of Ukrainian Gender Issues of the Early 20th Century - Марина Гринишина (Культура і мистецтво у сучасному світі, 2023)
The aim of the article is to analyse the genesis of Don Juan’s image and substantiate the imagology of the legendary character in the context of Ukrainian gender issues at the time Lesya Ukrainka wrote The Stone Master. Results. The article presents the basic principles of imagology as a comprehensive direction of cultural research and defines the meaning of using its tools in contemporary theatre studies. Attention is also paid to the gender studies of Ukrainian scholars, which are at the intersection with imagological issues. The study focuses on the image of Don Juan from the dramatic poem The Stone Master. The genesis of the character is traced from the 17th to the 19th century in order to demonstrate that his imagology is studied at the intersection of the stereotype concept and cultural iconography provisions. The Ukrainian poetess deliberately did not violate the canonical image of the seducer of Seville that was formed over three centuries. However, the obvious Byronic inspirations of the artistic ideology of the dramatic poem and the polemic with Hoffmannism and Nietzscheism, as well as gender issues, caused the transformation of the image, influenced the formation of the literary model, in a certain sense alien to the entire world context of the legend of Don Juan. Scientific novelty. For the first time in Ukrainian theatre studies, an attempt has been made to analyse the imagology of the legendary image created by Lesya Ukrainka in the context of Ukrainian gender issues at the beginning of the last century. Conclusions. The Stone Master, as well as a number of other dramatic poems by Lesya Ukrainka, provides rich factual material for research in the categories of imagology. They are facilitated by the transitive nature of the Ukrainian poetess’s dramatic works. Therefore, we consider the study of the images of foreign countries and peoples in a broad historical and cultural context based on Lesya Ukrainka’s dramatic poems to be one of the most promising directions of contemporary interdisciplinary research at the intersection of historical literature and theatre studies.